Expressive Writing Therapy: An Intervention for Uncovering Student’s Personal Issues - Suhertina; Nur'aini Safitri; Rina Rehayati; Nurhasnawati; Sariah; Rizky Adib Kurniaqil; Rizka Nurul Atika (Department of Guidance and Counseling, FIP, Undiksha, 2025)
This study was motivated by the importance of assisting university students in expressing personal problems that are often difficult to articulate verbally. The primary objective of the study was to analyze the effectiveness of expressive writing therapy in helping students express their personal problems and to identify the areas of problems they experience. The study employed a descriptive quantitative approach, with data analyzed using percentage calculations. The research subjects consisted of 60 students from the Islamic Educational Guidance and Counseling Study Program (BKPI). Data collection was conducted through the implementation of expressive writing therapy, using a systematically developed expressive writing guide as the research instrument. The results showed that 48 students (80%) were able to express their personal problems through expressive writing therapy. The most frequently expressed problem area was personal self-related issues (54.16%), followed by family circumstances and relationships (29.17%), romantic relationships and marriage (10.42%), education and instruction (4.17%), and economic and financial issues (2.08%). The study concludes that expressive writing therapy can serve as an effective alternative for counselors in assisting counselees, particularly those who experience difficulties in conveying problems verbally. The implication of this finding is that counselors may use expressive writing therapy as a primary approach or as a complementary technique within more integrative counseling services.